Вамыш: очеркъёс / Георгий Грязев - Грязев Георгий Геннадьевич (Удмуртия, 2014)
Экземпляры: Н. Армязьская библиотека (2017.20.12) / Инвентарный номер: 3919 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: Г 92 / ГРНТИ: 03.23.55 / ББК: 63.3(2Рос.Удм)